Monster & madman ebook - Niles, Steve (Monster & Madman (2014)., 2014)
The year is 1888 and the area of the city known as Whitechapel is about to become a slaughterhouse. Eleven women will be murdered. Only five will be attributed to Jack the Ripper. Discover the secret history of the Ripper and the Frankenstein Monster! Collects issues #1-3!